The Neuroprotective Flavonoids Sterubin and Fisetin Maintain Mitochondrial Health under Oxytotic/Ferroptotic Stress and Improve Bioenergetic Efficiency in HT22 Neuronal Cells - Marie Goujon; Zhibin Liang; David Soriano-Castell; Antonio Currais; Pamela Maher (MDPI AG, 2024)
The global increase in the aging population has led to a rise in many age-related diseases with continuing unmet therapeutic needs. Research into the molecular mechanisms underlying both aging and neurodegeneration has identified promising therapeutic targets, such as the oxytosis/ferroptosis cell death pathway, in which mitochondrial dysfunction plays a critical role. This study focused on sterubin and fisetin, two flavonoids from the natural pharmacopeia previously identified as strong inhibitors of the oxytosis/ferroptosis pathway. Here, we investigated the effects of the compounds on the mitochondrial physiology in HT22 hippocampal nerve cells under oxytotic/ferroptotic stress. We show that the compounds can restore mitochondrial homeostasis at the level of redox regulation, calcium uptake, biogenesis, fusion/fission dynamics, and modulation of respiration, leading to the enhancement of bioenergetic efficiency. However, mitochondria are not required for the neuroprotective effects of sterubin and fisetin, highlighting their diverse homeostatic impacts. Sterubin and fisetin, thus, provide opportunities to expand drug development strategies for anti-oxytotic/ferroptotic agents and offer new perspectives on the intricate interplay between mitochondrial function, cellular stress, and the pathophysiology of aging and age-related neurodegenerative disorders.